Testing comparison models of DASS-12 and its reliability among adolescents in Malaysia - Jamil Osman, Zubaidah; Mukhtar, Firdaus; Hashim, Hairul Anuar; Abdul Latiff, Latiffah; Mohd Sidik, Sherina; Awang, Hamidin; Ibrahim, Normala; Abdul Rahman, Hejar; Ismail, Siti Irma Fadhilah; Ibrahim, Faisal; Tajik, Esra; Othmana, Norlijah (Elsevier, 2014)
Objective The 21-item Depression, Anxiety and Stress Scale (DASS-21) is frequently used in non-clinical research to measure mental health factors among adults. However, previous studies have concluded that the 21 items are not stable for utilization among the adolescent population. Thus, the aims of this study are to examine the structure of the factors and to report on the reliability of the refined version of the DASS that consists of 12 items. Method A total of 2850 students (aged 13 to 17 years old) from three major ethnic in Malaysia completed the DASS-21. The study was conducted at 10 randomly selected secondary schools in the northern state of Peninsular Malaysia. The study population comprised secondary school students (Forms 1, 2 and 4) from the selected schools. Results Based on the results of the EFA stage, 12 items were included in a final CFA to test the fit of the model. Using maximum likelihood procedures to estimate the model, the selected fit indices indicated a close model fit (χ2 = 132.94, df = 57, p = .000; CFI = .96; RMR = .02; RMSEA = .04). Moreover, significant loadings of all the unstandardized regression weights implied an acceptable convergent validity. Besides the convergent validity of the item, a discriminant validity of the subscales was also evident from the moderate latent factor inter-correlations, which ranged from .62 to .75. The subscale reliability was further estimated using Cronbach's alpha and the adequate reliability of the subscales was obtained (Total = 76; Depression = .68; Anxiety = .53; Stress = .52). Conclusion The new version of the 12-item DASS for adolescents in Malaysia (DASS-12) is reliable and has a stable factor structure, and thus it is a useful instrument for distinguishing between depression, anxiety and stress.